2016
DOI: 10.1016/j.aop.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

The Wigner function in the relativistic quantum mechanics

Abstract: A detailed study is presented of the relativistic Wigner function for a quantum spinless particle evolving in time according to the Salpeter equation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…We have shown that such a program can be easily implemented within quantum mechanics for photon developed by I. Bia lynicki-Birula [2][3][4] and J. E. Sipe [5], and with the use of the continuous-discrete Wey -Wigner -Moyal formalism [1,9] (see also the wide bibliography therein). The result reinforces our believe that one can successfully apply this formalism to other relativistic particles thus obtaining a promising approach to searching for the relativistic Wigner functions [8,[26][27][28][29][30][31][32], although the problems with interpretation of the vector x are to be expected since for relativistic particles the operator x does not represent the position observable [23,25,[33][34][35][36][37][38][39]. So the natural question is if one can construct the Weyl -Wigner -Moyal formalism for photon employing the position operator introduced by Margaret Hawton [38].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We have shown that such a program can be easily implemented within quantum mechanics for photon developed by I. Bia lynicki-Birula [2][3][4] and J. E. Sipe [5], and with the use of the continuous-discrete Wey -Wigner -Moyal formalism [1,9] (see also the wide bibliography therein). The result reinforces our believe that one can successfully apply this formalism to other relativistic particles thus obtaining a promising approach to searching for the relativistic Wigner functions [8,[26][27][28][29][30][31][32], although the problems with interpretation of the vector x are to be expected since for relativistic particles the operator x does not represent the position observable [23,25,[33][34][35][36][37][38][39]. So the natural question is if one can construct the Weyl -Wigner -Moyal formalism for photon employing the position operator introduced by Margaret Hawton [38].…”
Section: Discussionsupporting
confidence: 83%
“…The results that were found, reinforce our belief that one can successfully apply this formalism to other relativistic particles in searching for their relativistic Wigner functions. [ 10,27–33 ] On the other hand the problems with interpretation of the vector truex are to be expected since for relativistic particles the operator truex̂ does not represent the position observable. [ 16,24,26,34–39 ] So the natural question arises if one can construct the Weyl – Wigner – Moyal formalism for photon employing the position operator introduced by Margaret Hawton.…”
Section: Discussionmentioning
confidence: 99%
“…Such a Wigner function can be made finite in the massless limit, analogously to Ref. [5] where a simplest example of this kind has been found.…”
mentioning
confidence: 78%
“…From this point of view, Spohn's equation emerges as the classical Koopman-von Neumann theory corresponding to the Dirac equation. The develop methodology can be readily apply to the analysis of other relativistic dynamical systems (e.g., governed by the Klein-Gordon equation [61,62]).…”
Section: Discussionmentioning
confidence: 99%